2010
DOI: 10.1371/journal.pone.0012305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Polycystin-1 Cleavage Product, P100, That Regulates Store Operated Ca2+ Entry through Interactions with STIM1

Abstract: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a genetic disorder resulting in large kidney cysts and eventual kidney failure. Mutations in either the PKD1 or PKD2/TRPP2 genes and their respective protein products, polycystin-1 (PC1) and polycystin-2 (PC2) result in ADPKD. PC2 is known to function as a non-selective cation channel, but PC1's function and the function of PC1 cleavage products are not well understood. Here we identify an endogenous PC1 cleavage product, P100, a 100 kDa fragment found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 40 publications
(61 reference statements)
4
68
1
Order By: Relevance
“…One possible explanation for the observed Pc1 deN excess (about 10-fold) is that Pc1 cFL at the plasma membrane continuously undergoes subunit dissociation followed by internalization and degradation of the resulting dissociated CTF via its cytoplasmic PEST domain (58)(59)(60). An alternative explanation for the finding is the previously described cleavage events in the C-terminal tail of the CTF (59,61,62), which may result in C-terminal fragments that are translocated to the nucleus for signaling (59,61). Since Pc1 deN is predicted to contain no TM domain, it may be associated to the membrane via another cell surface receptor(s) and/or by lipid modifications, as previously proposed for CIRL/ latrophilin and Sonic hedgehog (63,64).…”
Section: Discussionmentioning
confidence: 94%
“…One possible explanation for the observed Pc1 deN excess (about 10-fold) is that Pc1 cFL at the plasma membrane continuously undergoes subunit dissociation followed by internalization and degradation of the resulting dissociated CTF via its cytoplasmic PEST domain (58)(59)(60). An alternative explanation for the finding is the previously described cleavage events in the C-terminal tail of the CTF (59,61,62), which may result in C-terminal fragments that are translocated to the nucleus for signaling (59,61). Since Pc1 deN is predicted to contain no TM domain, it may be associated to the membrane via another cell surface receptor(s) and/or by lipid modifications, as previously proposed for CIRL/ latrophilin and Sonic hedgehog (63,64).…”
Section: Discussionmentioning
confidence: 94%
“…STIM1 serves as both the sensor of ER Ca 2ϩ levels and the activator of plasma membrane SOCs (6). Recent work has identified several SOCE regulatory proteins that appear to function by binding STIM1 (19,48,59,60). However, to our knowledge, STC2 represents the first ER luminal protein with the ability to both bind STIM1 and regulate the overall magnitude of SOCE.…”
Section: Discussionmentioning
confidence: 98%
“…6A, blue arrow). Cleavage at an equivalent position in Pkd1 has recently been described (Woodward et al, 2010), suggesting that this cleavage site is conserved between polycystin-1 family members. During our IP experiments, we found that the Pkd1l1-GFP 80 kDa band, which we named Pkd1l1_53, co-purified with Myc-PKD2 upon GFP or Myc IP (Fig.…”
Section: Pkd1l1 and Pkd2 Proteins Physically Interactmentioning
confidence: 94%